Factores sociodemográficos, laborales y su relación con el síndrome de burnout en cirujanos dentistas de atención primaria del Minsa – Iquitos, 2024 - Guerrero Sangama, Victor Enrique (2024)
Introduction: Burnout syndrome is a condition that affects the well-being of health professionals, particularly dental surgeons, due to work demands and sociodemographic factors that influence its development. This study addresses the situation of Burnout among primary care dental surgeons at MINSA in the city of Iquitos in 2024, exploring the associations between the syndrome and various factors. Objective: To determine the relationship between sociodemographic and work-related factors and the presence of Burnout syndrome in primary care dental surgeons at MINSA in Iquitos in 2024. Method: An observational, cross-sectional, and analytical study was conducted. Data collection was carried out using the MBI-HSS questionnaire and a sociodemographic-work questionnaire. Population: A sample of 57 primary care dental surgeons at MINSA in the city of Iquitos, selected representatively, was included. Results: The study found that 7.0% of the evaluated dental surgeons presented Burnout. Significant correlations were observed between the syndrome and factors such as marital status (p = 0.032), relationship duration (p = 0.048), job tenure (p = 0.049), and working hours (p = 0.042). The emotional exhaustion dimension was predominantly low in 52.6% of participants, while 43.9% reported high personal accomplishment. Conclusion: Burnout syndrome shows a low prevalence among dental surgeons in Iquitos, but the associations with specific factors highlight the importance of considering work and sociodemographic conditions when designing preventive interventions